Keratosis follicularis spinulosa decalvans: a family study of seven male cases and six female carriers. - van Osch, L D (1992)
Keratosis follicularis spinulosa decalvans (KFSD) is a rare X linked disease which is characterised by follicular hyperkeratosis of the skin and corneal dystrophy. Seven male patients and six female carriers are described. Special attention has been paid to the dermatological and ophthalmic markers of KFSD in patients and carriers. The most prominent features present in the male patients were follicular hyperkeratosis, hyperkeratosis of the calcaneal regions of the soles, scarring alopecia of the scalp, absence of eyebrows and eyelashes, and corneal dystrophy accompanied by photophobia. They also had high cuticles on the fingernails which has not been described before. Carriers often have dry skin, minimal follicular hyperkeratosis, and mild hyperkeratosis of the calcaneal areas of the soles. Mild corneal dystrophy without photophobia was observed in one female carrier.